2021
DOI: 10.1111/jhn.12972
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating nutrition education interventions for medical students: A rapid review

Abstract: Background: Unhealthy diets account for 20% of all deaths globally. Most medical schools do not sufficiently teach their students the clinical application of nutrition science. Evaluating the efficacy of nutrition education interventions is therefore important for their widespread implementation. Methods: A rapid review of the literature published between 2015 and 2020 was conducted to identify nutrition education interventions delivered to undergraduate medical students. The modified Kirkpatrick hierarchy sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 42 publications
(240 reference statements)
1
10
0
Order By: Relevance
“…As it was found in the study of Coleman et al [ 30 ], education in the first year of medical studies changed their dietary choices for the better and it may also impact the possibility to advise patients on nutrition in the future. A recent review [ 31 ] also showed that a variety of teaching approaches provided students with many benefits which are particularly important since an unhealthy diet is the cause of about 20% of deaths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As it was found in the study of Coleman et al [ 30 ], education in the first year of medical studies changed their dietary choices for the better and it may also impact the possibility to advise patients on nutrition in the future. A recent review [ 31 ] also showed that a variety of teaching approaches provided students with many benefits which are particularly important since an unhealthy diet is the cause of about 20% of deaths.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Axon et al [ 51 ], pharmacy students considered knowledge about dietary or herbal supplements as important, but they indicated that their knowledge was limited, which led to the conclusion that good education is necessary from the early years of medical majors. In general, it is stated that nutritional education is under-represented and underestimated in medical schools, and many medical school students reported inadequate knowledge and teaching methods that require employing more modern, interactive, and student-engaging approaches [ 31 ]. Different methods may be used to improve the students’ knowledge about DS or OTC drugs, especially in the experiential learning formulas, such as in-class activities (simulated patients) or work-based placements [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Culinary nutrition education has been proposed as an approach to engage other professions in nutrition education. Patel and Kassam 15 recently reviewed the need for nutrition training as medical education, highlighting not only the need for more education, but also the necessity for quality data to measure the impact on patient care. Ultimately, nutrition and dietetic education needs to be integrated at the appropriate level for all health professionals because nutrition is everyone's business.…”
Section: Embracing Other Approaches To Education and Training Other H...mentioning
confidence: 99%
“…28 This nutrition course offered to UCLA health professional students and medical students during the 2019 to 2020 academic year used a blended approach to deliver educational nutrition content including in-class didactics, interactive hands-on cooking sessions, and a servicelearning experience. 23,28,29 This upstream approach to increasing food literacy benefits medical students and future patients. 23,28,29 Lastly, students acknowledged the extremely problematic and common cultural issue of weight stigma.…”
Section: Nutrition Culture and Vulnerable Populationsmentioning
confidence: 99%